Understanding sustainable business model: A framework and a case study of the bike-sharing industry. (10th September 2020) - Gao, Ping; Li, Jiaying
Abstract: Supported by the Internet of Things (IoT) technology, bike-sharing services have become increasingly popular in recent years. For example, in China, by the end of 2017, the number of service users had doubled in half a year to reach 221 million users (28.6% of the country's Internet users); the market for bike-sharing services equated to £1.18 billion, an eightfold increase from 2016. In this research, we focus on the sustainability of the dockless bike-sharing industry, and analyze how firms achieve sustainability through innovating on business models to adapt to business environments. We have developed a framework of sustainable business model analysis that links business model innovation with the business environment. The sustainable value proposition dimension of the framework includes social-environmental benefits as an element. Applying this framework to analyze the case of Mobike, a leading dockless bike-sharing operator, we disclose the paths of its business model innovation in China and the UK determined by the business environment. The proposed framework can be used in future research of sustainable business model analysis and design. The case study findings extend knowledge about the emerging dockless bike-sharing industry. Practical implications are drawn from the case study for firms within the sharing economy to achieve sustainability through business model innovation, and for the government to support the sharing economy to achieve sustainable development. Highlights: A sustainable business model framework is developed. Sustainable value proposition includes the element social-environmental benefits. The framework links business model innovation with the business environment. A case study of dockless bike-sharing in China and the UK by Mobike is offered. Paths, factors for business model innovation differ for Mobike in China and the UK.